Echocardiographic determination of resting haemodynamics and optimal positioning in term pregnant women. (31st August 2018) - Dennis, A. T.; Buckley, A.; Mahendrayogam, T.; Castro, J. M.; Leeton, L.
Summary: Optimal positioning for anaesthesia in pregnant women involves balancing the need for ideal tracheal intubation conditions (achieved by the head elevated ramped position), with the prevention of reduced cardiac output from aortocaval compression (achieved by left lateral pelvic tilt). No studies have examined the effect on cardiac output of left lateral pelvic tilt in the ramped position. We studied non‐labouring, non‐anaesthetised healthy term pregnant women who underwent baseline (left lateral decubitus) cardiac assessment using transthoracic echocardiography. We then compared cardiac output, maternal physiological variables, fetal heart rate and comfort scores in three positions: left lateral decubitus; ramped position with wedge; and ramped position alone. Thirty women completed the study. Mean (SD) age, gestation and body mass index were 33.5 (3.93) years, 38.5 (0.94) weeks and 29.0 (4.0) kg.m −2, respectively. Mean ejection fraction, left ventricular internal diameter and mitral valve E/e' were 55.2 (6.8) %, 4.70 (0.43) cm and 7.50 (1.82), respectively. There were no differences in cardiac output between the positions (p = 0.503). There were no differences in systolic (p = 0.955) or diastolic (p = 0.987) blood pressure, maternal heart rate (p = 0.133), oxygen saturation, respiratory rate (p = 0.964) or fetal heart rate (p = 0.361) between ramped with wedge and ramped alone positions. Left lateral decubitus was most comfortable (p = 0.001), however, there were no differences in comfort levels between ramped with wedge and ramped alone positions. The ramped position without left lateral tilt is safe and acceptable in non‐labouring, non‐anaesthetised, healthy term pregnant women. Left lateral pelvic tilt may be unnecessary in the head elevated ramped position in term pregnant women.